2009
DOI: 10.1889/jsid17.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic depth perception survives significant interocular luminance differences

Abstract: Abstract— The effects of interocular luminance differences on stereoscopic depth perception has been investigated. The stimuli were stereoscopic square‐shaped targets created from disparity embedded in a dynamic random‐dot stereogram, which eliminated other cues to depth perception. The results revealed that stereoscopic depth perception survived significant interocular differences in luminance levels, even up to differences of 60%, provided that display luminance was approximately 0.63 cd/m2 or higher. In ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Human stereo depth perception appears to be surprisingly robust despite significant interocular differences in luminance level or stimulus contrast. With respect to luminance level, it has been reported 16 that stereoscopic depth perception, as indexed by perceived depth measurements and depth discrimination thresholds, was relatively unaffected by interocular luminance differences of up to 60%. Visual discomfort has been studied 15 and it was found that only slight discomfort occurs with interocular luminance differences of up to 25%; accordingly, these authors concluded that the threshold for significant discomfort was greater than 25%.…”
Section: Interocular Differences In Luminance and Contrastmentioning
confidence: 99%
“…Human stereo depth perception appears to be surprisingly robust despite significant interocular differences in luminance level or stimulus contrast. With respect to luminance level, it has been reported 16 that stereoscopic depth perception, as indexed by perceived depth measurements and depth discrimination thresholds, was relatively unaffected by interocular luminance differences of up to 60%. Visual discomfort has been studied 15 and it was found that only slight discomfort occurs with interocular luminance differences of up to 25%; accordingly, these authors concluded that the threshold for significant discomfort was greater than 25%.…”
Section: Interocular Differences In Luminance and Contrastmentioning
confidence: 99%
“…Perceived depth of a virtual object in a stereo display is computed as: d = (D m × S)/ (I ± S), where d is predicted depth (in meters), D m is viewing distance in meters, S is separation between half-images on the display screen (in meters), and I is interpupillary distance (in meters); when disparity is crossed, the denominator is (I + S), and when disparity is uncrossed, the denominator is (I − S) (Cormack & Fox, 1985b). Perceived depth in a stereoscopic display does vary in accord with this relation (Boydstun, Rogers, Tripp, & Patterson, 2009;Patterson et al, 1995;Patterson, Moe, & Hewitt, 1992;Richards, 2009;Ritter, 1977;Wallach & Zuckerman, 1963). Here, the visual system may recalibrate the disparity for different egocentric viewing distances but the recalibration derived from real-world viewing becomes misapplied when a stereo display is viewed.…”
Section: Disparity Change With Egocentric Viewing Distance In Stereo mentioning
confidence: 98%
“…3.2 , for previous discussion of the Pulfrich effect, a spurious depth effect, that occurs with interocular differences in luminance of over 10 % and moving images.) Boydstun, Rogers, Tripp, and Patterson ( 2009 ) reported that stereoscopic depth perception (indexed by perceived depth measurements and depth discrimination thresholds) was relatively unaffected by interocular luminance differences of up to 60 %. Visual discomfort was studied by Kooi and Toet ( 2004 ) and they found that only slight discomfort was reported with interocular luminance differences of up to 25 %; above 25 % discomfort was greater.…”
Section: Interocular Differences In Luminancementioning
confidence: 99%
“…7 There is a vast amount of literature that surrounds several aspects of 3D capture, image processing, and displays. 8,9,10,11,12 In particular, there are several human factors topics, such as accommodation-vergence, that deal with 3D viewing comfort. 8,9 This paper will focus on the measurable attributes and application-specific considerations for selecting and ruggedizing 3D display hardware for a robust stereo-vision-system application.…”
Section: Teleoperation Using 3d Remote Viewing Systemmentioning
confidence: 99%